An analysis of renewable energy resources and options for the energy transition in Chile - Oyarzún Aravena, Andrea María; Chen, Jiying; Brownbridge, George; Akroyd, Jethro; Kraft, Markus (My University, 2025)
This study analyses renewable energy resources, infrastructure, and practical options to accelerate the energy transition and unlock Chile's potential as an exporter of renewable energy and products. We analyse data on the potential of wind and solar energy to determine the best areas for renewable projects. The progress of the energy transition occurring in Chile is reviewed in the context of historical events. The abundant renewable energy resources far exceed current demand and offer exceptional harvesting conditions. However, geographical limitations and a lack of enabling infrastructure may limit the participation of Chile in the world net-zero economy. A comparison is made with the UK to provide a broader perspective. This identifies order-of- magnitude differences in the power available in different locations, highlighting the importance of considering where best to deploy limited resources. International cooperation is required to make the best use of the available renewable energy. Three practical international options to unlock Chile's potential are discussed. Further technical-economic assessment of these energy-transition acceleration paths is recommended. The data and results are integrated into a set of 2D/3D visualisations, facilitating visual insights and enabling a comprehensive understanding of the challenges and opportunities facing Chile.
Keywords: energy transition; sustainability; renewable energy; green hydrogen; chile; 2d/3d visualisation